Design an Interfacing Tracking System in Rehabilitation Therapies Between The Elbow Joint of The Human Arm and The Prosthetic Arm - Yee, Low Cheng; Nemah, Mohammed Najeh; Ismail, Al Emran (International Journal of Integrated Engineering, 2020)
Myoelectric prostheses have seen an increased application in clinical practice and research, due to their potential for good functionality and versatility. Yet, myoelectric prostheses still suffer from a lack of intuitive control and haptic feedback, which can frustrate users and lead to abandonment. To address this problem, a prosthetic arm was designed to help the amputees, who unfortunately lost their upper limb. Then, the prosthetic arm was equipped with a hybrid haptic feedback stimulation system to compensate for the missing sensation and enable the amputees to easily perform their normal life activities. The tracking system between the elbow joints of the human and the prosthetic arms was required to accomplish the experimental tests with the able-body subjects. Accordingly, this study is a platform for the main project. The major problem is to synchronize the movements of the prosthetic arm’s elbow joint with the human arm’s elbow joint within a high response, acceptable accuracy, and low error. Therefore, the PID controller was used to control the tracking system and the flexible bending sensor was attached to the volunteer’s elbow joint to record its rotational movements. The results verified the functionality of the proposed tracking system to synchronize the joints movements and enable the prosthetic arm to follow the movements of the volunteer’s arm within 0.062 sec. Finally, the effectiveness of the proposed elbow joints tracking system to synchronize the motions of the volunteer and he prosthetic arms was concluded.